Cryptic speciation in populations of the genus Aphyocharax (Characiformes: Characidae) from eastern Amazon coastal river drainages and surroundings revealed by single locus species delimitation methods - Brito,Pâmella S. (2021)
Abstract Recent studies in eastern Amazon coastal drainages and their surroundings have revealed new fish species that sometimes exhibit little morphological differentiation (cryptic species). Thus, we used a DNA-based species delimitation approach to test if populations showing the morphotype and typical character states of the Aphyocharax avary holotype correspond either to A. avary or A. brevicaudatus, two known species from the region, or if they form independent lineages, indicating cryptic speciation. WP and GMYC analyses recovered five lineages (species) in the ingroup, while a bPTP analysis delimited three lineages. ABGD analyses produced two possible results: one corroborating the WP and GMYC methods and another corroborating the bPTP method. All methods indicate undescribed cryptic species in the region and show variation from at least 1 to 4 species in the ingroup, depending on the approach, corroborating previous studies, and revealing this region as a possible hotspot for discovering undescribed fish species.